(untitled) (Journal of Additive Manufacturing Technologies, 2022)
The number of 3D printer filament development studies are increasing day by day by using composite materials to respond the need to create implants which have personalized design by using fused deposition modelling (FDM) 3D printing technology in bone tissue engineering. The aim of this study is to investigate the effect of Hydroxyapatite content in properties of composites and to produce filaments from developed composite materials. 10%, 15%, 20% and 25 wt. % Hydroxyapatite (HA) filled Polycarbonate (PC) composite granules were produced by using twin-screw extruder. Filaments were produced by filament production line. Characterization samples were obtained by using hot press in accordance with the standard dimensions. Density and MFI (Melt Flow Index) measurements, thermogravimetric analysis (TGA), and mechanical tests including tensile, three-point bending, and Izod un-notched impact strength tests are performed. Scanning Electron Microscopy (SEM) analysis was carried out to investigate the morphological changes. Tensile strength and elongation at break values were decreased but Young’s modulus was increased with increasing amount of HA in the composition. Similar results were obtained for flexural tests. Izod impact strength values were decreased by increasing HA amount. 3D printer filaments were produced and flexural test specimens were printed in 3D printer.